Plasticity of Cardiovascular Chemoreflexes After Prolonged Unilateral Carotid Body Denervation: Implications for Its Therapeutic Use - Eugenin-Leon, J (American Physiological Society, 2020)
Eugenín J, Larraín C, Zapata P. Plasticity of cardiovascular chemoreflexes after prolonged unilateral carotid body denervation: implications for its therapeutic use. Am J Physiol Heart Circ Physiol 318: H1325 H1336, 2020. First published April 24, 2020; doi: 10.1152/ajpheart.00451.2019. Unilateral carotid body denervation has been proposed as treatment for sympathetic-related human diseases such as systolic heart failure, hypertension, obstructive sleep apnea, and cardiometabolic diseases. The long-Term therapeutic effects of carotid body removal will be maintained if the remnant "buffer nerves," that is, the contralateral carotid nerve and the aortic nerves that innervate second-order neurons at the solitary tract nuclei (NTS), do not modify their contributions to the cardiovascular chemoreflexes. Here, we studied the cardiovascular chemoreflexes 1 mo after unilateral carotid body denervation either by excision of the petrosal ganglion (petrosal ganglionectomy, which eliminates central carotid afferents) or exeresis of a segment of one carotid nerve (carotid neurectomy, which preserves central afferents). Cardiovascular chemoreflexes were induced by intravenous (iv) injections of sodium cyanide in pentobarbitone-Anesthetized adult cats. After 1 mo of unilateral petrosal ganglionectomy, without significant changes in basal arterial pressure, the contribution of the contralateral carotid nerve to the chemoreflex increases in arterial pressure was enhanced without changes in the contribution provided by the aortic nerves. By contrast, after 1 mo of unilateral carotid neurectomy, the contribution of remnant buffer nerves to cardiovascular chemoreflexes remained unmodified. These results indicate that a carotid nerve interruption involving denervation of second-order chemosensory neurons at the NTS will trigger cardiovascular chemoreflex plasticity on the contralateral carotid pathway. Then, unilateral carotid body denervation as therapeutic tool should consider the maintenance of the integrity of carotid central chemoafferents to prevent plasticity on remnant buffer nerves. NEW and NOTEWORTHY Unilateral carotid body denervation has been proposed as treatment for sympathetic hyperactivity-related human disorders. Its therapeutic effectiveness for maintaining a persistent decrease in the sympathetic outflow activity will depend on the absence of compensatory chemoreflex plasticity in the remnant carotid and aortic afferents. Here, we suggest that the integrity of central afferents after carotid body denervation is essential to prevent the emergence of plastic functional changes on the contralateral "intact" carotid nerve. © 2020 American Physiological Society. All rights reserved.